2019
DOI: 10.1021/acs.inorgchem.8b03366
|View full text |Cite
|
Sign up to set email alerts
|

Cycloosmathioborane Compounds: Other Manifestations of the Hückel Aromaticity

Abstract: The discovery of cycloosmathioborane compounds is reported. These species, which are prepared by the simultaneous dehydrogenation of a trihydride hydrogensulfide osmium(IV) complex and a BH 3 NHR 2 amine−borane, bear an Os−S−B three-membered ring, being a manifestation of the 4n + 2 Huckel aromaticity in which n = 0 and where the two π electrons of the ring are provided by the S atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The aromatic characteristics of metallaaromatics have become a topic of intense debate. ,, It has been shown that studying the aromaticity in these systems is not a trivial task, and many new phenomena, which have not been previously detected in analogous organic compounds, appear. ,,, For instance, aromaticity of monocyclic conjugated hydrocarbons and their heteroatom derivatives can be rationalized by several electron counting aromaticity rules . On the other hand, even in the most simple monocyclic metallaaromatics, there is an ongoing debate on how many electrons are involved in cyclic conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…The aromatic characteristics of metallaaromatics have become a topic of intense debate. ,, It has been shown that studying the aromaticity in these systems is not a trivial task, and many new phenomena, which have not been previously detected in analogous organic compounds, appear. ,,, For instance, aromaticity of monocyclic conjugated hydrocarbons and their heteroatom derivatives can be rationalized by several electron counting aromaticity rules . On the other hand, even in the most simple monocyclic metallaaromatics, there is an ongoing debate on how many electrons are involved in cyclic conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…According to such ability, xant­(P i Pr 2 ) 2 is adapted to the requirements of the reactions in which its complexes participate, enabling the necessary geometrical transformations on the metal coordination sphere through changes in its coordination mode . As proof-of-concept validation, besides species bearing the diphosphine κ 3 - P , O , P - mer coordinated, complexes with the ligand in fashions κ 3 - P , O , P - fac , κ 2 - P , P - cis , and κ 2 - P , P - trans , have been also isolated. This is allowing to perform reactions and to isolate compounds initially forbidden, and as result, interesting catalysts for a wide range of processes are being discovered. ,,, The proved flexibility and great coordinative versatility of xant­(P i Pr 2 ) 2 inspired us to use it to address the preparation of a neutral hydride-osmium­(II)-allenylidene complex.…”
Section: Introductionmentioning
confidence: 99%
“…Osmapentalenes and osmapentalynes are known. , However, pincer complexes of this element are scarce in comparison with the number of known compounds for the rest of the platinum-group metals. The pincer ligands coordinated to this element mainly involve neutral or monoanionic , moieties, which result from the simple coordination of tridentate molecules or the coordination of bidentate groups along with the σ-bond activation of one of their substituents, whereas osmium complexes bearing dianionic pincer ligands are very rare. Examples include C,C′,N-donors, which are generated by coordination of a 2e-donor N atom and two σ-bond activations at the molecule skeleton, or O,N,O-, C,C′,C-, and C,N,C-donors, which are formed as a consequence of the coordination of a 2e-donor atom and a σ-bond activation at two substituents of the molecular core. …”
Section: Introductionmentioning
confidence: 99%